The effects of nickel tungstate nanoparticles (NiWO4 NPs) on freshwater microalga Raphidocelis subcapitata (Chlorophyceae) - de Abreu, Cínthia Bruno (2025)
Among the vast array of functional nanoparticles (NPs) under development, nickel tungstate (NiWO4) has gained prominence due to its potential applications as a catalyst, sensor, and in the development of supercapacitors. Consequently, new studies on the environmental impact of this material must be conducted to establish a regulatory framework for its management. This work aims to assess the effects of NiWO4 (NPs) on multiple endpoints (e.g., growth, photosynthetic activity, and morphological and biochemical levels) of the freshwater microalga Raphidocelis subcapitata (Chlorophyceae). Quantification data revealed that the fraction of dissolved Ni and free Ni2+ increased proportionally with NiWO4 NP concentrations, although these levels remained relatively low. Biological results indicated that NiWO4 NPs did not inhibit the growth of algal cells, except at 7.9 mg L−1, resulting in a 9% decrease. Morphological changes were observed in cell size and complexity, accompanied by physiological alterations, such as a reduction in chlorophyll a fluorescence (FL3-H) and signs of impaired photosynthetic activity, indicated by the effective quantum yield, quenchings, and chlorophyll a (Chl a) content. Furthermore, the rapid light curves showed that the NPs in high concentrations affected microalga ability to tolerate high light intensities, as corroborated by the significant decrease in the relative electron transport rate (rETRmax) and saturation irradiance (Ek). Based on the present study results, we emphasize the importance of applying integrative approaches in ecotoxicological studies, since each endpoint evaluated showed different sensitivity.